A Case of Subacute Encephalopathy Developing After Treatment With Clofarabine and Methotrexate That Resolved With Corticosteroids. (May 2016) - Tzachanis, Dimitrios; Haider, Mintallah; Papazisis, Georgios
Abstract : This is the case of a 24-year-old woman with relapsed acute undifferentiated leukemia who developed subacute encephalopathy with hemiparesis and dysarthria after treatment with high dose and intrathecal methotrexate, clofarabine, and cytarabine that resolved rapidly and completely after the administration of corticosteroids. We hypothesize that clofarabine might predispose to methotrexate-induced central nervous system toxicity by increasing endothelial permeability (capillary leak syndrome) and suggest that corticosteroids are effective in the treatment of this type of encephalopathy.